2018
DOI: 10.1200/jco.2018.78.4777
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer Risks for PMS2-Associated Lynch Syndrome

Abstract: Heterozygous PMS2 mutation carriers were at small increased risk for colorectal and endometrial cancer but not for any other Lynch syndrome-associated cancer. This finding justifies that PMS2-specific screening protocols could be restricted to colonoscopies. The role of risk-reducing hysterectomy and bilateral salpingo-oophorectomy for PMS2 mutation carriers needs further discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 42 publications
7
131
2
2
Order By: Relevance
“…It is therefore highly likely that if the authors had carried out incidence ratios for those individuals testing negative for mis-match repair (MMR) and other PV, they would have demonstrated an increased risk with a cumulative risk to age 60 years of over 25%; and (iv) The authors have not reported whether the variants segregated with disease which would at least have provided some supportive data. Whilst the authors state that 'the risks of other cancers, including breast are less clearly delineated' this ignores most of the negative evidence available [2,4].…”
mentioning
confidence: 99%
“…It is therefore highly likely that if the authors had carried out incidence ratios for those individuals testing negative for mis-match repair (MMR) and other PV, they would have demonstrated an increased risk with a cumulative risk to age 60 years of over 25%; and (iv) The authors have not reported whether the variants segregated with disease which would at least have provided some supportive data. Whilst the authors state that 'the risks of other cancers, including breast are less clearly delineated' this ignores most of the negative evidence available [2,4].…”
mentioning
confidence: 99%
“…The assay also offers a means to investigate Lynch syndrome where CMMRD is a plausible explanation for an exceptional phenotype, given that it can distinguish between patients with mono‐ versus biallelic MMR variants. For example, it is recognized that pathogenic PMS2 variants are less penetrant than other MMR gene variants in the context of Lynch syndrome (Møller et al, ; Ten Broeke et al, ), yet approximately 8% of CRCs in carriers of pathogenic PMS2 variants are diagnosed before the age of 30 and in the distal colon, much earlier than the mean onset at 48 years in probands and distinct from the proximal location that is typical of Lynch syndrome (Goodenberger et al, ). Similarly, CMMRD patients with hypomorphic PMS2 variants have a predominance of colorectal (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the phenotypic overlap with NF1 and Legius syndrome has led to the acknowledgment of CMMRD as a legitimate, but presumably rare, differential diagnosis in children without malignancy who are suspected of these syndromes but lack the causative NF1 or SPRED1 variants (Suerink et al, ). Family history can also be misleading as pathogenic variants in PMS2 , the gene implicated in more than 50% of CMMRD cases (Wimmer et al, ), have a much lower penetrance than other MMR variants in Lynch syndrome (Møller et al, ; Ten Broeke et al, ). Hence, the C4CMMRD criteria were designed to have high diagnostic sensitivity at the cost of specificity, and detection of pathogenic variants in both alleles of an MMR gene is required to confirm the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The most common genetic susceptibility for CRC is Lynch syndrome (LS)-also being one of the most common hereditary cancer syndrome [2]. Patients with LS have markedly increased lifetime risk of CRC and endometrial cancer (EC), as well as ovarian, gastric, hepatobiliary, bladder, renal, brain, breast, prostate, small intestine, pancreatic and sebaceous skin cancers [3][4][5][6][7]. The penetrance of LS is approximately 52% for CRC, 57% for EC, 38% for ovarian, and less than 20% for other previously mentioned cancers [8].…”
Section: Introductionmentioning
confidence: 99%